Computational Fluid Dynamics (CFD) Simulation of Sand Particle Erosion in Turbulent Gas Fluid Flow in Vertical-Horizontal Elbow - Ido Widya Yudhatama; Mas Irfan Purbawanto; Wikan Jatimurti (Jurnal Teknik ITS, 2018)
Erosion of sand particles is one of the serious problems in the oil and gas production industry. There is strong evidence that most wells now produce increased sand as the major oil and gas production declines. This is a widespread problem as it can affect the rate of production as we age the asset. Accurate erosion prediction, especially elbow, can be used to improve pipe work design, inspection area, operating limit and others. In this study, we used CFD modeling in ANSYS Student Version 19.0 application to predict erosion in turbulent gas flow with the variation of sand particle size and fluid velocity. The results obtained were erosion profile and erosion rate in pipe elbow compared with the experimental results. Simulation results show that CFD able to predict erosion rates well for 300 μm particle size with error 14.75% compare 150 μm particle size with error 271.5%. Formed erosion profile in the form of 'V' scar on the vertical - horizontal pipe elbow.